The effect of skatole and androstenone on consumer response towards streaky bacon and pork belly roll. (December 2015) - Aaslyng, Margit D.; De Lichtenberg Broge, Eva Honnens; Brockhoff, Per B.; Christensen, Rune Haubo
Abstract: Consumer liking was assessed for streaky bacon and pork belly roll from entire male pigs with an androstenone (AND) content of up to 9.4 ppm and a skatole (SKA) content of up to 0.92 ppm in the back fat and castrates. No clear effect of either AND or SKA was seen in consumer liking, although an insignificant tendency was seen for SKA. A sensory profile analysis showed that AND increased the boar taint of bacon, while both AND and SKA increased the boar taint of the pork belly roll. Consumer sensitivity towards AND and SKA did not affect liking of the meat products. The lack of effect of AND and SKA on consumer liking could be due to a masking effect of the spices and smoke. Three consecutive weeks' exposure to bacon did not change the liking score, irrespective of the AND and SKA content. This indicates that the consumers did not become more sensitive towards boar taint. Highlights: No effect of androstenone was seen on consumer liking of bacon or pork belly roll. A tendency towards an effect of skatole on consumer liking of the meat products Androstenone has an impact on the sensory quality of bacon and pork belly roll. Skatole has a small impact on the sensory quality of the meat products. In general, no significant effect was found on consumer sensitivity towards androstenone.